2022
DOI: 10.1002/solr.202200266
|View full text |Cite
|
Sign up to set email alerts
|

Downconversion Materials for Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) have made game‐changing progress in the last decade and reached a power conversion efficiency (PCE) of up to 25%. Furthermore, the development of material chemistry, structure design, active layer composition, process engineering, etc. has contributed to improving PSCs’ stability. The significant PCE losses experienced by PSCs are related to spectral mismatch between the incident solar spectra and absorption range of the active layer, which thereby limits the PCE. Besides PSCs’ pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 190 publications
(224 reference statements)
0
11
0
Order By: Relevance
“…The doping of YOSe with Eu and Tb significantly improved the absorbance and luminescence properties of YOSe and through the preliminary PV device performances obtained, the newly synthesized YOSe:Tb and YOSe: Eu nanomaterials can be used as good light-absorbing materials for standalone PV devices, or incorporated in already established PV devices to boost their performance or for tandem PV device application. [89][90][91][92]…”
Section: Electrovoltaic and Photovoltaic Analysesmentioning
confidence: 99%
“…The doping of YOSe with Eu and Tb significantly improved the absorbance and luminescence properties of YOSe and through the preliminary PV device performances obtained, the newly synthesized YOSe:Tb and YOSe: Eu nanomaterials can be used as good light-absorbing materials for standalone PV devices, or incorporated in already established PV devices to boost their performance or for tandem PV device application. [89][90][91][92]…”
Section: Electrovoltaic and Photovoltaic Analysesmentioning
confidence: 99%
“…34 For inorganic materials (QDs and lanthanide nanoparticles) the topic has been extensively covered by others. 32,[35][36][37] We will not discuss these materials in depth, but recognise that the challenges in QD based MEG are related to modest yield, as well as how to efficiently extract the multiple excited states due to their often ultrashort lifetimes. [38][39][40] Instead, we will focus on singlet fission (SF), a multiexciton generation process in organic molecules.…”
Section: Overcoming the Sq Limit: Mitigating Losses Through Photon Co...mentioning
confidence: 99%
“…Further improving the effective absorption of the solar spectrum is an important measure to continue the improvement of solar cell efficiency [1][2][3][4]. Some research has shown that compared with other types of high-efficiency silicon solar cells, heterojunction cells showed worse spectrum response in the short wavelength region [5].…”
Section: Introductionmentioning
confidence: 99%